MODES ET PRATIQUES D’ACCESSION AU POUVOIR COUTUMIER A L’ERE CONTEMPORAINE : CAS DES BINDJI-NGUSU, SECTEUR LUKIBU EN PROVINCE DU KASAÏ CENTRAL - KABUJI BUALU Gabriel; MUTOMBO TSHINAYI ANTOINE (IJRDO - Journal of Social Science and Humanities Research, 2019)
The Bundji-Ngusu people localised in a geographical surface are located enters 22 33’ of Southern altitude and 29 21’ longitude Is, with a surface of 5070Km² for a population of 99.348 inhabitants.¶ Bundji-Ngusu are subject to the influence of the climates heat and wet, with two seasons:¶dry six (6) months and rainy six (6) months.¶The ground Bindji is clay-sand.¶ Bindji are limited:¶ - In North by the Territory of Kole (Province of Sankuru);¶ ¶- In the South by the Territory Demba (Kasaï-Exchange);¶ ¶- In the West by the Territories of Mweka and Ndekese (Province of Kasaï);¶ ¶- In the East by the Sector of Mashala (Province Kasaï-Exchange).¶ The people draw their origins in High Katanga, in a place located at Nsanga-in-Lubanga, not far from Kamina with an ancestor common Luba.¶ The spoken language is Cibindji, classified in the Zone LA / 22 in code 805, according to classification congolaise.¶They are organized in family in the broad sense with a patrilineal system.¶ The Bindji Company is well structured, in family, clan, tribe and the respect of elder, the parents, the authorities is of strict rigour and nonthe observance would involve harmful consequences on health.¶ The dance, the music, the proverbs, clothing are categorized according to circumstances’ and the age group.¶Each gesture, laughter, glance, step are followed of very near by the inhabitants.¶ The marriage took account of the virginity of the girl, because it gave more honor.¶Art Bindji is observed in the linguistic expression, in the songs and dances.